MANAGEMENT DALAM GEREJA KATOLIK: YA ATAU TIDAK? - Gitowiratmo, St. (Jurnal Orientasi Baru, 2015)
Managerial issues are rencently emerging as a new topic of pastoral discusions. The main question is: if there is possibility to combine some or many managerial principles and pastoral services in Catholic Church. The background of the question is a new understanding about being and becoming a Chruch in the modern world. The management sciences on leaderships and its strategic planning critically asked to the Catholic leaders: “how do the pastoral activities be arranged? How do the financial resources for pastoral purposes be managed? How do the pastoral human resources be planned? Etc. Questioning them the managerial sciences are opening a new perspective in the Church regarding to the role of management and its posibility to serve pastoral activities in the Church. But the Church, in the same time, is completely aware of her identity as firstly a spiritual body. She is a living community of Christians by faith. She is, however, a visible community as a sosial body which is able to be understood as an organizational entity. With her hyrarchical and leadershipsystems, her Cannon Law and its implementations, and her pastoral activities, the Church, no doubtly, is doing a series of managerial actions. This article puts in light the close relationship between the managerial principles and pastoral practices of Church.